1999
DOI: 10.1155/1999/743628
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Emergency Department Visits for Asthma

Abstract: BACKGROUND: Asthma can usually be controlled through allergen avoidance and/or appropriate medication. An emergency department visit for an acute exacerbation of asthma often represents a breakdown in asthma management. Emergency department treatment results in significant health care expenditures and reflects a compromised quality of life. OBJECTIVES: To identify risk factors associated with an emergency department visit for asthma. METHODS: This case-control study compared 299 people (76% of 390 cases contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The office and CLSC accessibility index, recently developed in Quebec, will allow us to investigate this further in the future. Our data suggest that a significant proportion of the population seeking care at the ED may be undiagnosed and undertreated (37,38). For the zero to four years age group, the concentration of high-morbidity areas in the south-central region of the province raises the question of the role of potential nonmedical, environmental or other factors.…”
Section: Discussionmentioning
confidence: 79%
“…The office and CLSC accessibility index, recently developed in Quebec, will allow us to investigate this further in the future. Our data suggest that a significant proportion of the population seeking care at the ED may be undiagnosed and undertreated (37,38). For the zero to four years age group, the concentration of high-morbidity areas in the south-central region of the province raises the question of the role of potential nonmedical, environmental or other factors.…”
Section: Discussionmentioning
confidence: 79%
“…5,12,17,39,40 Our findings differ from those of previous studies that found female sex to be a risk factor for increased acute asthmarelated resource utilization. 8,11,41,42 Sex, however, has not consistently been related to hospitalization, 7,14,22,43 and some studies found that males have greater health care use, particularly in the inner city. 20,44,45 Race and ethnicity have been also associated with higher risk of acute health care resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Many demographic, clinical, utilization, medication, and social/environmental factors have been associated with an increased risk of acute asthma-related resource utilization. Among the most consistent risk factors reported were sex, lower socioeconomic status, more clinically severe asthma (including previous utilization), and increased use of rescue medications.…”
mentioning
confidence: 99%
“…Studies have shown that such interventions can reduce ED and hospital utilization in high-risk patients with asthma. [4][5][6][7][8] Many studies have used clinical information [9][10][11][12] or computerized administrative data [13][14][15][16] to define risk factors for subsequent asthma utilization. Validated psychometric tools demonstrate reliability and validity across multiple domains and represent another source of potentially useful predictors of subsequent asthma resource utilization.…”
mentioning
confidence: 99%